Recognising the homely in an unheimlich world : rationality and the uncanny ecosphere - Lingesh, Dhanya (Nanyang Technological University, 2021)
This thesis investigates how the uncanny facilitates an individual’s return to the Real truths of the ecological world and to an affective and authentic self, by forcing them to recognise the problematic nature of their faith in widely accepted rational and scientific ‘realities’, which are often deliberately manipulated or augmented to conceal what is truthfully Real. I argue that this process of recognition and homecoming is evident in Indra Sinha’s Animal’s People (2007) and two of Amitav Ghosh’s novels, The Hungry Tide (2004) and Gun Island (2019). Through the development of a more ecologically-minded strain of reason, these novels prove that a reconnection to the wider nonhuman ecosphere helps individuals surmount humanity’s increasingly ubiquitous sense of loneliness, thus furthering their recognition of place and purpose. I also suggest that romance is a literary tool that not only seizes the reader’s attention but also allows us to appreciate how isolated urbanites are simply lonely souls seeking lost connections to the Real. It does this as an extension of the uncanny, and in the mode of what I have dubbed as the romantic uncanny.